Physical characterization of BiFeO3‐based thin films with enhanced properties for photovoltaic applications. Issue 11 (14th July 2022) - Mariano, Marcos A. S.; Mendez‐González, Yanela; Silva, Atair C.; Monte, Adamo F. G.; Lima, Elton C.; Guo, Ruyan; Bhalla, Amar S.; de los Santos Guerra, José
Abstract: The present paper reports the multifunctional properties of lead‐free BiFeO3 –La (BFO–La) thin films. The structural, microstructural, and optical properties have been investigated as a function of the lanthanum doping concentration. The structural properties at room temperature showed the formation of the perovskite structure, thus suggesting the high quality of the obtained thin film compositions. Raman spectroscopy analysis revealed a slight variation in both the peak position and absolute intensity for the Raman active modes, as lanthanum content increases in BiFeO3 –La. Crystallized thin films with well‐defined grains as well as crack‐free surfaces have been obtained, for all the studied compositions, as inferred from atomic force microscopy images. The optical properties have been measured, and the values for the direct bandgap was significantly lower than those reported for other BFO‐based systems, being the lowest ∼1.87 eV for the Bi0.90 La0.10 FeO3 composition. Results revealed a noteworthy effect of the defect concentrations induced by the lanthanum doping on the long‐range crystallinity and directly affecting the polarizability of the A–O bond as well as the Fe–O and Fe–O–Fe bond lengths in the perovskite structure. The enhanced optical absorption properties registered for the Bi1– x La x FeO3 ( x = 0–20) compositions make these perovskite multiferroic thin films as a potential candidate material for the high‐performance photovoltaic device applications.